I looked at back and saw the future - Saidova Visola Komil qizi (Genius Publishing Group, 2023)
This article discusses the significant place of our national fabrics and traditional dress. We will look at the major revolutions in the history of Uzbek national costume and its impact in our time
Keywords: National fabrics and costumes; culture; fashion industry